DYNAMIC LOAD SIMULATION OF 4WD SUV AND FATIGUE LIFE ANALYSIS OF FRAME - GE WenTao; LIU Zhou; DUAN LongYang; JIA HuiFang; GONG ChunHui (Jixie qiangdu)
In order to predict fatigue life of frame,the MBS model of full vehicle has been built,based on the road load data,by applying virtual iteration technique,the dynamic load of interface point of frame has been obtained. In order to solver the time-consuming problem of dynamic load simulation caused by off-road in durability procedure,the road has been reduced by applying time correlated fatigue analysis with damage editing method,the value and distribution of damage are same as the original one,the mileage of single loop has been reduced to 1. 6 Km from original 3 Km,the dynamic load simulation has been accelerated. The fatigue life of frame has been predicted by applying Miner Counting Algorithm for Acuminated Fatigue Analysis,the analysis result has shown that the fatigue life can satisfy the target,and the vehicle has ultimately passed the durability validation of proving ground,which has shown that the analysis result is accorded with the test.